2020
DOI: 10.18502/jad.v14i1.2715
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Antimicrobial Resistance Patterns of Bacterial Species Isolated from the Body Surface of the Housefly (Musca domestica) in Akure, Ondo State, Nigeria

Abstract: Background: The emergence and spread of antibiotic resistant bacteria has become a serious problem worldwide. House­flies are potential carriers of pathogenic and resistant bacteria and could be contributing to the global spread of these strains in the environments.We investigated the prevalence and antimicrobial resistant profiles of bacteria isolated from houseflies in Akure. Methods: Twenty-five houseflies were captured by a sterile nylon net from the slaughterhouse, garbage dump, human house, hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Ertapenem (96.25% of susceptible isolates), trimethoprim-sulfamethoxazole (91.25% of susceptible isolates), aztreonam (88.75% of susceptible isolates), ciprofloxacin (85.00% of susceptible isolates), and gentamicin (88.75% of susceptible isolates) were the most effective antimicrobials against the tested Enterobacteriaceae isolates. This is in line with the results reported by other authors [ 25 , 42 , 43 ], with few works reporting higher percentages of resistant isolates [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Ertapenem (96.25% of susceptible isolates), trimethoprim-sulfamethoxazole (91.25% of susceptible isolates), aztreonam (88.75% of susceptible isolates), ciprofloxacin (85.00% of susceptible isolates), and gentamicin (88.75% of susceptible isolates) were the most effective antimicrobials against the tested Enterobacteriaceae isolates. This is in line with the results reported by other authors [ 25 , 42 , 43 ], with few works reporting higher percentages of resistant isolates [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In another survey on MDR isolates carried by flies in dairy farms, the percentages of MDR E. coli ranged between 3.17% and 44.44% [ 21 ]. In a study on antimicrobial resistance in bacteria isolated from house flies, collected in different settings, the percentage of MDR Enterobacteriaceae ranged between 5.9% and 50% [ 43 ]. Poudel and coworkers identified 19.04% of MDR E. coli and 5.4% of MDR K. pneumoniae among isolates coming from flies collected in different locations [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial resistance results in a serious public health problem, for it weakens the treatment efficacy against bacterial infections and this poses greater health risks (Russell et al, 2018;Wei et al, 2013). Some studies have reported some bacterial isolates which are resistant to significantly more than one of the commonly used antibiotics tested (Akter et al, 2020;Hemmatinezhad et al, 2015;Nazari et al, 2017;Nwankwo et al, 2020;Odentoyin et al, 2020;Rahuma et al, 2005). According to Russell et al (2018), dipterans that associate with livestock, livestock waste products and cadavers have the potential to acquire livestock-associated antibiotic resistant bacteria and transmit them to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Flies are important reservoirs and vectors of antimicrobial resistant bacteria (such as methicillin resistant Staphylococcus aureus , ESBL-producing Enterobacterales [ESBL-E]) 3 , 7 . One short report suggests that antimicrobial resistant bacteria can also be detected in flies (n = 25) in sub-Saharan Africa 8 . However, the true burden of AMR in ‘filth flies’ in Africa is unknown and it is currently unclear which fly species are the main vectors of ESBL-E and enteropathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%